(untitled) (Memorias Sifored - Encuentros Educación UAN, 2021)
The outbreak of COVID-19 coronavirus infection in Wuhan and the spreading through the globe forced the governments to rapidly adopt drastic measures to ensure the safety of the population. The effects of these restrictions negatively impact all social and work sectors f the global population te reset their life. In the educational system, The pandemic leads to the near-total closures of schools, universities and colleges and reorganize the educational approach. School closures impact not only has consequences on the students, teachers, and family’s life but also economic and societal. The impact of the Russian government decision to face the pandemic crisis in all level of the public education system and the ability of the educational institute to readapt to the new reality is the topic of the presented manuscript. The main issues, advantages and effect on students, academic workers and families related to the reorganization of the educational system are reported. The effect of the restriction, together with the new learning approach on the mental health of the student in the Russian Federation, is reported. Although all the resources successfully employed by the Russian Federation to quickly counteract the diffusion of the virus, long term strategies have to be adopted to preserve and ensure a wealthy and healthy life of the population.